The effect of technology implementation in providing drug information on consumer satisfaction in Jakarta, Indonesia - Noviani, Lusy; rachmawati, Putriana; Octavioni, Octavioni (Faculty of Pharmacy, Universitas Pancasila, 2024)
The provision of drug information (PDI) is a crucial factor influencing consumer behavior and ensuring appropriate drug use, thereby achieving therapeutic goals. With advancements in technology, digital platforms such as tele-counseling, WhatsApp, and social media are increasingly being used for PDI. However, challenges such as unclear communication, incomplete information, and delayed responses remain, which may affect consumer satisfaction. This study aims to assess consumer satisfaction with PDI through the implementation of a pharmacy application, using the End User Computing Satisfaction (EUCS) model, which evaluates information content, accuracy, format, ease of use, and timeliness. The research employed an associative, cross-sectional design and involved 250 consumers at Atma Jaya Pharmacy. Data were collected via a Likert-scale-based questionnaire, with responses analyzed to determine satisfaction levels in each EUCS dimension. Results showed that consumer satisfaction was consistently high across all dimensions, with the average satisfaction scores being 89.10% for information content, 90.19% for accuracy, 87.25% for format, 85.33% for ease of use, and 86.78% for timeliness. In conclusion, the use of technology in PDI significantly enhances consumer satisfaction, offering more accessible, accurate, and timely drug information. This study highlights the importance of optimizing technological tools in pharmaceutical services to improve user experience and satisfaction.